Time evolution of ion-acoustic double layers in an unmagnetized plasma - Bharuthram, R.; Momoniat, E.; Mahomed, F.; Singh, S.V.; Islam, M.K. (My University, 2008)
Ion-acoustic double layers are examined in an unmagnetized, three-component plasma consisting of cold ions and two temperature electrons. Both of the electrons are considered to be Boltzmann distributed and the ions follow the usual fluid dynamicalequations. Using the method of characteristics, a time-dependent solution for ion-acoustic double layers is obtained. Results of the findings may have important consequences for the real time satellite observations in the space environment.
Keywords: Ion acoustic waves; Plasma; Ion-acoustic double layers